2017
DOI: 10.4103/ijmm.ijmm_16_186
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Ventilator-associated Pneumonia and Impact of Multidrug-Resistant Infections on Patient’s Outcome: Experience at an Apex Trauma Centre in North India

Abstract: Isolation of MDR pathogens from bronchoalveolar lavage does not always adversely affect the outcome of patients. It requires an interdisciplinary team of clinical microbiologists, physicians and hospital infection control nurses, to collectively manage these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The study done by Khurana et al in North India also showed similar results. 16 49.10% Pseudomonas aeruginosa isolates showed resistance to ceftazidime and 54.55% to ciprofloxacin. Similar results were documented in a study conducted by Ilkunur Erdem et al which showed 59% of Pseudomonas aeruginosa isolates were resistant to ceftazidime and 62% to ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…The study done by Khurana et al in North India also showed similar results. 16 49.10% Pseudomonas aeruginosa isolates showed resistance to ceftazidime and 54.55% to ciprofloxacin. Similar results were documented in a study conducted by Ilkunur Erdem et al which showed 59% of Pseudomonas aeruginosa isolates were resistant to ceftazidime and 62% to ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of its affliction in India is limited to a few clinical studies [14][15][16][17] and fewer environmental studies 15,18 . There is a need to prioritize studies on this unexplored pathogen as the rates of ventilator associated pneumonia is fairly larger in India 19,20 . Though conventional culture technique is considered the gold standard for detection, use of molecular techniques like PCR have proven to increase the sensitivity for clinical diagnosis of Legionella [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of monitoring of the individual compliance with these strategies may hide the role of unmeasured confounding factors. Another prospective study by Khurana et al, designed to assess the impact of VAP and MDR germs on critically ill patients, highlighted the inverse correlation between VAP incidence and preventive measures compliance (ventilator bundle plus hand hygiene) trends [ 89 ]. Again, the decline in VAP rate observed in young and old patients admitted to French ICUs between 2007 and 2014 (aIRR 95%CI 0.88, 0.82–0.94, p < 0.001 and 0.89, 0.81–0.98, p = 0.022, respectively) was partially explained by the improvement of ventilator bundle adherence over time [ 90 ].…”
Section: Combining the Strategiesmentioning
confidence: 99%